A Novel Sensitive and Selective Amperometric Detection Platform for the Vanillin Content in Real Samples. Issue 6 (31st March 2021) - Karakaya, Serkan; Kaya, İsmet
Abstract: Accurate and sensitive determination of vanillin in commercial samples is significant for food safety & quality. In the proposed study, copper particles were coated on an indium tin oxide electrode (ITO) by cyclic voltammetry (CV) for the determination of vanillin in food samples. CV studies indicated that the electrodeposition of Cu particles provides a good electrocatalytic effect towards the oxidation of vanillin. The fabricated sensor determines vanillin linearly between 0.50 μM–2.0 mM (Limit of detection: 0.15 μM). The Cu/ITO was successfully tested on vanillin samples and the recommended method provides accurate and selective determination of vanillin in daily samples. Abstract :